IMPLEMENTASI KEBIJAKAN PROMOSI POTENSI WISATA ( PANTAI WIDURI) KABUPATEN PEMALANG - Kusumawardhani, Dyah; Rostyaningsih, Dewi; Rengga, Aloysius (Journal of Public Policy and Management Review, 2016)
Tourism is one of the construction sector which is currently being promoted by the government into the background of this research. The problem that arises: Implementation of promotion policy of the government tourism potential Pemalang Objective To describe the implementation of the research for policy promotion of tourism potential in Pemalang. Efforts to address concerns and purpose of the study conducted using qualitative approach in addressing the issues contained in the Department of Culture and Tourism Pemalang. The results showed forms of promotion done by the Department of Tourism and Culture Pemalang include: promotion in the form Personal selling is done through exhibitions and events. Inhibiting factors include the readiness of the development gap between the attractions with incessant promotion that has been conducted by the Department of Tourism and Culture and related parties does not occur effectively. Advised the Department of Tourism and Culture Pemalang optimize all forms of promotion of tourism in the district of Pemalang district so as to attract visitors significantly through the cooperation of the tourism business.